2014
DOI: 10.1007/s10980-014-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Managing landscape heterogeneity in different socio-ecological contexts: contrasting cases from central Loess Plateau of China and southern Finland

Abstract: Context Landscape transition drives environmental change across the globe. However, landscape and its change are complex with high spatial heterogeneity, which challenges strategic decision-making. Objectives This paper aims to derive management meaningful units based on landscape status and change analysis and the generalization of landscape spatial heterogeneity. Methods Based on contrasting cases from Finland (Vanajavesi) and China (Baota District), this paper analyzed the landscape attributes and change si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Its rugged landform is composed of steep hills, gullies, and loess soil susceptible to water erosion. Consequently, soil and water conservation, re-vegetation, and engineering measures have been implemented in this area since the early 1950s (Lü et al 2015).…”
Section: Study Areamentioning
confidence: 99%
“…Its rugged landform is composed of steep hills, gullies, and loess soil susceptible to water erosion. Consequently, soil and water conservation, re-vegetation, and engineering measures have been implemented in this area since the early 1950s (Lü et al 2015).…”
Section: Study Areamentioning
confidence: 99%
“…The integrated assessment highlights the importance of taking account of the complex interactions between different sectors under varied scenarios in planning adaptation strategies. Lü et al (2014) analyzed landscape transition based on contrasting cases from Finland (Vanajavesi basin) and China (Baota District of Yan'an city). A k-means clustering approach was used to generalize the landscape types based on indicators of landscape composition and its change, spatial pattern, population, and income.…”
Section: About This Special Issuementioning
confidence: 99%
“…Then, it examines the evolution of territorial space from different development perspectives. Other studies identified areas with a high risk of expan-sion of urban built-up areas and shrinkage of farmland in the future on the premise of simulating land use change and then proposed a reference scheme to optimize LUSP (Lu et al, 2015). The literature review above indicates that the RECC and LUC have a profoundly close relationship with the supply of territorial space and are mutually influential and restrictive.…”
Section: Introductionmentioning
confidence: 99%